Hearing loss in patients using isotretinoin: is it a side effect or due to hyperlipidemia? - Fatih Boztepe, O.; Alan, Sevil; Murat Özcan, K.; Erdem Gür, Ö.; Gün, Taylan (ENT Updates, 2013)
Objective: To prospectively investigate the effect of isotretinoin therapy on the functions of hearing and to show the relationship between concurrent triglyceride levels. Methods: A total of 47 patients who were admitted to our dermatology clinic between February 2011 and June 2011 for the treatment of acne using 0.5 mg/kg isotretinoin were included in this study. All the patients were started on 0.5 mg/kg/day isotretinoin depending on their tolerance of the drug. Details such as age, sex, dose of isotretinoin for the first 6 months, monthly pretreatment and posttreatment, and ALT, AST, triglyceride and total cholesterol values were recorded. There were 33 females and 14 males in the study group. Results: Audiometric evaluations made prior to treatment with isotretinoin, levels of PTA1 and PTA2 were 11.96 and 12.59, respectively, these were compared with the results of tests carried out after the treatment and pre- and posttreatment values of PTA1 and PTA2 were found to be the same, 1 month after the treatment, drug use did not effect hearing. PTA 1 value after 3 months was 12.16 and PTA 2 value was 13.85. These values are compared to pretreatment values and PTA2 PTA1 both were decreased. However, in the third month the threshold decrease was not statistically significant (p>0.05). PTA1 and PTA2 values after the sixth month were 12.25 and 12.96, this decrease was statistically significant compared with pretreatment values (p<0.05). Conclusion: Treatment with isotretinoin increased total cholesterol and triglyceride levels. Isotretinoin reduced pure-tone average hearing at the end of the 6th month and this effect was related to the increases in the levels of triglycerides and total cholesterol.